Strategi edukasi anti perundungan (bullying) di SDN 1 Kota Ternate melalui pendekatan interaktif Board Game - Muhammad, Hujaefa Hi; Ali, Silvani Umar; Supriyono, Yusup; Putri, Ismi Oktalia; Abdu, Irawati (ABSYARA: Jurnal Pengabdian Pada Masayarakat, 2024)
Bullying in schools is a pressing issue, particularly at the elementary level. Data from the Indonesian Child Protection Commission (KPAI) indicates that 28% of students have experienced violence, while 29% have acted as perpetrators. This community service activity aimed to enhance students' understanding of anti-bullying behavior through the use of board games, creating a child-friendly classroom environment at SDN 1 Kota Ternate. The implementation consisted of three stages: preparation, execution, and evaluation. Fifth-grade students participated in interactive education using board games, involving case studies and attitude assessments through pretest and posttest evaluations. The results showed increased students' understanding of anti-bullying behavior, with the average pretest score of 65.3 rising to 85.7 in the posttest. The board game effectively created an engaging learning atmosphere, fostered social interaction, and helped students internalize anti-bullying values. This program significantly contributed to creating a child-friendly school environment and preventing bullying behavior from an early age.